Notice of some Human and other Remains recently found at Kelso (Proceedings of the Society of Antiquaries of Scotland, 1865)
This paper reports that while digging drains at the East end of Kelso Abbey, excavators uncovered several cists. The author describes some of these burial sites and their contents. He concludes that the newer burials were from the reign of Edward VI and that the older from the medieval period.